Ammonia plant design - Jocson, Dominador; Ledesma, Russel; Merritt, Pedro (Diliman, Quezon City College of Engineering, 1968)
This is a report on the study of the feasibility of a synthetic ammonia plant, using the process developed by the Nitrogen Engineering Corporation. This process may be broken down into three basic steps, i.e. production of the synthesis gas, purification, and subsequent conversion of N2 and H2 to NH3. The figures, based on the design of a plant with an annual production rate of 3,300 tons, and a selling price of P1.00/lb, are the following: Operation: 330 days/year (24-hr day) -- Fixed capital investment: 2,369,370 -- Total product cost: 490,504 -- Product value: 1,150,000 -- Gross profit: 659,496 -- Pay-out time: 2.5 yrs. -- Break-even point: 31% -- Return on capital: 23%. The conclusion drawn from these figures is that a plant operating under these conditions will be economically profitable.
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design
Keywords: Factories -- Design and construction; Chemical plants; Ammonia industry